Biomonitoring of substrates containing sewage sludge: assessment of the feasibility in using the diplopod Rhinocricus padbergi. - Fontanetti, C.S.; Nogarol, L.R.; Souza, R.B.; Bozzatto, V.; Perez, D.G. (My University, 2012)
Due to the constant release of potentially harmful substances in the environment, it is necessary the use of biomonitoring as a form to assess the impact of these substances on animals that inhabit this environment. Therefore, there is a better understanding of the possible effects that these exogenous substances may cause in the organisms present there. In the present study it was verified the feasibility of the use of the diplopod Rhinocricus padbergi as bioindicator of impacted soils by their exposition to substrates containing different concentrations of sewage sludge from different Sewage Treatment Stations (STSs). It was observed animals' behavior and the survival rate was analyzed by log-rank test (p=0,05). The analysis showed that the animals exposed to pure sewage sludge presented higher mortality index than the specimens exposed to different concentrations of the sludge mixed with soil. In general, the survival rate and the analysis of the behavior of the diplopod R. padbergi showed efficiency of this species in biomonitoring impacted soils.